EVALUATION OF ECONOMIZER HEAT TRANSFER IN BOILER RECOVERY UNITS IN PULP FACTORY - Panjaitan, Jabosar Ronggur Hamonangan; Manurung, Anggun Theresia; Galingging, Vanisa Helena; Purba, Sasro Arif (Universitas Muhammadiyah Surakarta, 2025)
A boiler generates steam by principally exchanging heat. The economizer helps heat the feed water as part of a boiler system. Economizer and boiler functions predictably can improve heat transfer efficiency. Specifically, this study's research method for heat transfer and economizer efficiency of the boiler is in the pulp production plant unit. The heat transfer coefficient and efficiency were calculated based on water temperature and flue gas entering and exiting the economizer. Based on this research, it was found that during the second to fourth-day evaluation, the heat transfer effectiveness and heat transfer coefficient were low. The lowest economizer heat transfer effectiveness on the second day was 72%. Meanwhile, the lowest economizer heat transfer coefficient on the fourth day was 925 W/m2K. The low value of the heat transfer effectiveness and heat transfer coefficient can be caused by scaling in the economizer, so heat transfer was not optimal. The higher the value of heat transfer effectiveness in the economizer, the more flue gas heat will be extracted. Maximum heat transfer can be reached by the economizer cleaning process to remove the scaling, so heat transfer between flue gas and water occurs maximally.